Moral Values And The Upbringing Of Youth (Zien Journal of Social Sciences and Humanities, 2025)
This article is about increasing orrortunities for intercultural communication in the country and region as a whole, in the context of increasing the orrortunities for cultural communication and today, in the context of innnovation, intellectual Oriental Renaissance.